Screening of wheat genotypes against salinity at early vegetative stage in pot culture - Uddin, MS; Hossain, KMW (Bangladesh Journal of Botany, 2018)
Experiment was carried out to investigate intraspecific variation for salt tolerance and to classify the wheat genotypes into different salt tolerant groups. Considerable variations among the genotypes in response to salinity were observed for shoot length under 16 dS/m NaCl salinity in the both seasons. Salt tolerant genotype was found to be less affected at high salinity and could be produced better total dry matter compared to other genotypes. Five and seven genotypes appeared as tolerance during 2008 - 09 and 2009 - 10, respectively based on relative total dry matter (RTDM). On the other hand, six and three genotypes exhibited tolerant during 2008 - 09 and 2009 - 10, respectively based on visual scoring. The distribution pattern of the genotypes into various salinity tolerant groups remained fairly constant under two methods. Three genotypes G24, G33 and G40 exhibited tolerant category. RTDM compared to the control would be very useful trait in salinity tolerant improvement programme. However, visual scoring provide guidelines for mass screening of salt tolerant genotypes.